ESTIMASI PERMINTAAN DAN NILAI EKONOMI TAMAN WISATA ALAM ANGKE KAPUK JAKARTA UTARA - Vanna Fitriana; Zainal Abidin; Teguh Endaryanto (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The objectives of this research were  to identify factors affecting tourist visit frequencies, estimate economic value, and identify factors affecting in attractiveness of Angke Kapuk Nature Park.  This research employed quantitaive descriptive method.  The research data were collected in January 2017 using  a survey method.  Sample size was 77 respondents who were selected by using accidental sampling.  Poisson regression was used to analyze factors affecting tourist visit frequencies, travel cost method was used to estimate economic value and Partial Least Square was used to analyze attractiveness of Angke Kapuk Nature Park.  The study showed that tourist visit frequencies was affected by travel cost, visitor’s age, income per month mangrove forest condition, facilities, and services; based on travel cost method,  economic value of Angke Kapuk Nature Park was Rp.10,606,271,602 per year; Attractiveness of Angke Kapuk Nature Park was affected by natural beauty directly. Key words:  mangrove forest, tourism attarctiveness, travel cost method